Patterns of ocular sarcoidosis at a tertiary eye center in Nepal - Subedi, Kumudini; Shrestha, Smita; Manandhar, Anu (Journal of Karnali Academy of Health Sciences, 2021)
Background: Sarcoidosis has been identified as a chronic granulomatous disease involving multiple organ systems, including the eye. Having an unknown incidence and prevalence and closely mimicking tuberculosis which has high prevalence, this disease is often misdiagnosed. This study has been undertaken to assess the patterns of presentation of sarcoid uveitis in a tertiary level eye hospital in Nepal. Methods: This was a retrospective observational study based on Electronic Medical Recording (EMR). 35 patients fulfilling International Workshop on Ocular sarcoidosis (IWOS) criteria for ocular sarcoidosis were included in the study and clinical signs and symptoms were studied. Ethical clearance was attained from institutional review board of Tilganga Institute of Ophthalmology (Ref. no 16/2020) Associations were sought regarding the type of uveitis, either granulomatous or non-granulomatous and demographic parameters of age and gender and other characteristics like IWOS group and presence of an increased Angiotensin Converting enzyme (ACE) and involvement of anterior segment or not. Chi-square test was used to find the level of significance and p value of <0.05 was considered statistically significant. Results: The most common pattern of occurrence of ocular sarcoidosis was bilateral disease (82.8%) with panuveitis (39%) being the most common anatomical involvement followed by anterior with intermediate uveitis (29%), isolated anterior uveitis (23%) and posterior uveitis (7%). There was no disparity regarding age, gender, caste or habitat in the occurrence of ocular sarcoidosis. Granulomatous inflammation (62.85%) was more common than non-granulomatous (31.42%) and was significantly more common in people >40 years old (p=0.036). Conclusion: Sarcoidosis should be considered in the differential diagnosis of any uveitis as sarcoidosis has no known prevalence and yet extremely variable ocular presentation